PERAN LINGKUNGAN DALAM PENDIDIKAN ISLAM BERDASARKAN ALQURAN DAN HADITS: Penelitian Library Research (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT The environment plays a crucial role in Islamic education because it is the primary factor in shaping students' morals, character, and mindset. The Qur'an demonstrates that the learning process requires a conducive environment (QS. Al-'Alaq 1–5), the family serves as the primary bulwark for developing faith and morals (QS. At-Tahrim 6), and the social environment can strengthen or damage a person's character (QS. Al-Furqan 27–29). The Prophet's hadith emphasizes that education must be built on exemplary behavior (uswah hasanah) and an atmosphere of compassion and tenderness (rahmah and rifq), as moral values ​​are more effectively instilled through concrete examples and empathetic relationships. Therefore, Islamic education can only succeed if the entire environment—family, school, community, and even social interaction spaces—work together to create a religious atmosphere, full of exemplary behavior, and supportive of the development of noble morals in students.